2010
DOI: 10.1590/s0004-27492010000500008
|View full text |Cite
|
Sign up to set email alerts
|

Lente de contato escleral na reabilitação ocular de pacientes com síndrome de Stevens-Johnson

Abstract: RESUMOObjetivo: Avaliar a eficácia do uso das lentes de contato esclerais no manejo das sequelas oculares de pacientes portadores de síndrome de StevensJohnson. Métodos: Foram avaliados, retrospectivamente, pacientes com sequelas oculares da síndrome de Stevens-Johnson que iniciaram o uso de lente de contato escleral. Os pacientes foram submetidos a avaliação subjetiva dos sintomas através de um questionário; exame oftalmológico (medida da acuidade visual, biomicroscopia, coloração da superfície ocular com col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Various studies have shown the extensive use of scleral contact lenses (especially BOSP [Boston ocular surface prosthesis] and PROSE) in addressing the problems related to ocular discomfort, improving visual acuity and various ocular surface parameters such as Ocular Surface Disease Index (OSDI), visual function questionnaire 25 (VFQ-25), and National Eye Institute (NEI) grading in patients with various ocular surface diseases [ Table 3 ]. [ 1 , 32 - 44 ]…”
Section: Scleral Contact Lensesmentioning
confidence: 99%
“…Various studies have shown the extensive use of scleral contact lenses (especially BOSP [Boston ocular surface prosthesis] and PROSE) in addressing the problems related to ocular discomfort, improving visual acuity and various ocular surface parameters such as Ocular Surface Disease Index (OSDI), visual function questionnaire 25 (VFQ-25), and National Eye Institute (NEI) grading in patients with various ocular surface diseases [ Table 3 ]. [ 1 , 32 - 44 ]…”
Section: Scleral Contact Lensesmentioning
confidence: 99%